Popular Graeco-Roman mythology-based expressions as company names that identify a business profile - Puda-Blokesz , Magdalena (Papers in Linguistics, 2022)
The article attempts to demonstrate functional aspects of popular Graeco-Roman mythology-based expressions which occur in Polish chrematonymy that assume the role of proper company names, with particular emphasis on their function as business profile and business subtype identifiers. First, the extralinguistic background, that is the reality of consumer culture and competitive market, is outlined. The theory of marketing communication between the company and the customer is referred to, as are business names (company names mostly) forming one of the persuasive elements in this communication. Finally, description of data extracted from the pkt.pl company list is presented, including names with such components as Atena, Wenus, Herkules, Cerber, Hades, Styks and Charon as well as industry classification for particular business activities. The analysis of the source material made it possible to determine functions of mythology-based company names. Meant to produce in their recipients the relevant connotations (and associations) governed by the cultural semantic baggage, besides the core functions ascribed to onyms, such names also serve the informative and identifying, persuasive and axiological, culture-forming and socialising roles, among others. The considerations put forward here are situated in the domain of onomastics related to cultural chrematonymy.